Transcranial Direct Current Stimulation over the Medial Prefrontal Cortex and Left Primary Motor Cortex (mPFC-lPMC) Affects Subjective Beauty but Not Ugliness - Nakamura, Koyo; Kawabata, Hideaki (Frontiers in Human Neuroscience, 2015)
Neuroaesthetics has been searching for the neural bases of the subjective experience of beauty. It has been demonstrated that neural activities in the medial prefrontal cortex (mPFC) and the left primary motor cortex (lPMC) correlate with the subjective experience of beauty. Although beauty and ugliness seem to be semantically and conceptually opposite, it is still unknown whether these two evaluations represent extreme opposites in unitary or bivariate dimensions. In this study, we applied transcranial direct current stimulation (tDCS) to examine whether noninvasive brain stimulation modulates two types of aesthetic evaluation; evaluating beauty and ugliness. Participants rated the subjective beauty and ugliness of abstract paintings before and after the application of tDCS. Application of cathodal tDCS over the mPFC with anode electrode over the lPMC, which induced temporal inhibition of neural excitability of the mPFC, led to a decrease in beauty ratings but not ugliness ratings. There were no changes in ratings of both beauty and ugliness when applying anodal tDCS or sham stimulation over the mPFC. Results from our experiment indicate that the mPFC and the lPMC have a causal role in generating the subjective experience of beauty, with beauty and ugliness evaluations constituting two distinct dimensions.